Higher Detection Rates of Biologically Aggressive Breast Cancers in Mammography Screening than in the Biennial Interval - Prange, Anna; Bokhof, Beate; Polzer, Philipp; Tio, Joke; Radke, Isabel; Heidinger, Oliver; Heindel, Walter; Weigel, Stefanie (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose Assessment of age group-dependent detection rates of invasive breast cancers among participants in mammography screening including the interval, classified into immunohistochemical subtypes indicating the intrinsic tumor aggressiveness.Materials und Methods The target population comprises women aged 50 – 69 years. All invasive breast cancers diagnosed in one screening (sc) unit during the implementation phase 1/2006 – 12/2010 or identified by the cancer registry during the biennial interval (iv) were categorized based on hormonal-receptor status (HR) and Her2-expression (Her2) into the following subtypes: a) HR+ Her2-, b) HR+ Her2 +, c) HR– Her2 + or d) HR– Her2– (triple-negative); Her2 + and triple-negative types were defined as aggressive. The calculated detection rates (DR, ‰) were based on 53 375 sc-examinations and for the interval on 52 887 sc-negative examinations.Results The DRs of all subtypes were higher in screening versus the interval: (a) 4.95 ‰ (n = 264) vs. 1.00 ‰ (n = 53); b) 0.92 ‰ (n = 49) vs. 0.25 ‰ (n = 13); c) 0.36 ‰ (n = 19) vs. 0.06 ‰ (n = 3); d) 0.39 ‰ (n = 21) vs. 0.19 ‰ (n = 10). 77.4 ‰ (89/115) of all aggressive breast cancers including the following 2-year interval were diagnosed by screening. The sum of the DR of aggressive cancers was 1.67 ‰ in screening and 0.49 ‰ in the interval; the corresponding DRs for women aged 60 – 69 years [sc: 2.24 ‰ (51/22 814), iv: 0.58 ‰ (13/22 536)] were higher than among women aged 50 – 59 years [sc: 1.24 ‰ (38/30 561), iv: 0.43 ‰ (13/30 351)].Conclusion Screening has the potential for earlier diagnosis of aggressive tumor types as its detection rate is about three-fold higher compared to the interval. Within the target group, participants aged 60 – 69 years are at risk based on absolute numbers. They show a nearly two-fold higher detection rate of Her2-positive or triple-negative tumors compared to the age group 50 – 59 years.Key Points Citation FormatZielsetzung Ermittlung der altersgruppenabhängigen Detektionsraten invasiver Mammakarzinome im Mammografie-Screening einschließlich des Intervalls, differenziert nach immunhistochemischer Subtypisierung als Parameter der intrinsischen Tumoraggressivität.Material und Methode Die Zielgruppe sind 50 – 69-jährige Frauen. Alle in einer Screening-Einheit während der Implementierungsphase 1/2006 – 12/2010 in Screening (Sc)-Untersuchungen und im folgenden 2-jährigen Intervall (Iv) diagnostizierten invasiven Mammakarzinome wurden anhand des Hormonrezeptorstatus (HR) und der Her2-Expression (Her2) folgenden Subtypengruppen zugeordnet: a) HR+ Her2-, b) HR+ Her2 +, c) HR– Her2 + oder d) HR– Her2– (triple-negativ); Her2 + und triple-negativ wurden als aggressiv definiert. Die ermittelten Detektionsraten (DR, ‰) basierten auf 53 375 Sc-Untersuchungen und für das Intervall auf 52 887 Sc-negativen Untersuchungen.Ergebnisse Die DR aller Subtypengruppen waren im Screening höher als im Intervall: (a) 4,95 ‰ (n = 264) vs. 1,00 ‰ (n = 53); b) 0,92 ‰ (n = 49) vs. 0,25 ‰ (n = 13); c) 0,36 ‰ (n = 19) vs. 0,06 ‰ (n = 3); d) 0,39‰ (n = 21) vs. 0,19‰ (n = 10). 77,4 ‰ (89/115) aller aggressiven Mammakarzinome einschließlich des folgenden 2-Jahresintervalls wurden im Screening diagnostiziert. Die Summe der DR aggressiver Karzinome betrug im Screening 1,67‰ und im Intervall 0,49 ‰; dabei lagen die DR bei den 60 – 69-Jährigen [Sc: 2,24 ‰ (51/22 814), Iv: 0,58‰ (13/22 536)] höher als bei den 50 – 59-Jährigen [Sc: 1,24‰ (38/30 561), Iv: 0,43‰ (13/30 351)].Schlussfolgerung Screening hat das Potenzial einer Diagnosevorverlagerung aggressiver Tumorsubtypen bei einer etwa 3-fach höheren Detektionsrate als im Intervall. In der Zielgruppe bilden 60 – 69-Jährige bezüglich der absoluten Diagnosehäufigkeit eine Risikogruppe mit einer nahezu doppelten Detektionsrate Her2-positiver oder triple-negativer Tumoren im Vergleich zu 50 – 59-Jährigen.Kernaussagen Zitierweise
Keywords: breast cancer; mammography screening; interval breast cancer; tumor subtypes; cancer characteristics